Pluralistic economics and its history - Sinha, Ajit; Thomas, Alex M. (Routledge, 2019)
"This volume is a history of economics -- as it was interpreted, discussed and established as a discipline -- in the 20th century. It highlights the pluralism of the discipline and brings together leading voices in the field who reflect on their lifelong work. The essays in this draw on a host of traditions of economic thought -- including Pre-Classical, Classical, Marxian, Neoclassical, Sraffian, Post-Keynesian, Cantabrigian, and Institutionalist traditions in economics. Further, the volume also looks at the history of economics in India and its evolution as a discipline since the country's independence. This book will appeal to students, researchers and teachers of economics, intellectual history, as well as to the interested general reader"--